The need to establish a pre-marriage course regulation in Indonesia with special reference to Jambi province - Ahmadi, Faisal (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
A Pre-Marriage Course is a course on the circumstances of marriage carried out before the couples go through the marriage world. The purpose of the pre-marriage course is to guide and give knowledge about the principles of marriage to couples who want to get married. The lack of knowledge and marital responsibility has contributed to the breakdown of marriages among Indonesian couples. The study adapts doctrinal and qualitative analysis of data obtained from textbooks and statutory laws. In addition, data is collected from the Jambi province to answer problems associated with marital conflicts. A sample of pre-marriage course as practised in Malaysia is examined to provide guidelines and model the implementation of the course. Thus, the researcher argues that a pre-marriage course in Indonesia in general and especially in Jambi province is very important to be in practice, before couples perform marriages. Therefore, the study is undertaken to introduce a pre-marriage course in minimising marital conflicts. Compulsory pre-marriage course is expected to provide an understanding on the principles of knowledge about the ins and outs of marriage to a prospective husband and wife in the realisation of the purpose of family institution based on Islam.